(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Environments can be designed to be health enhancing. The Govan–Partick Bridge, a new major walking and cycling river bridge in Glasgow (UK), aims to promote active travel, reduce motorised transport and contribute to Glasgow’s net-zero climate goals. A comprehensive two-year evaluation is underway to assess the bridge’s impact on active travel, wellbeing, and transport. This study explores users’ early experiences and how the bridge has influenced their physical activity, wellbeing, and travel behaviour in the initial weeks after opening. Methods: The Govan–Partick Bridge opened on 7th September 2024, with baseline intercept surveys conducted in September and October 2024, and with 12-month and 2-year follow-ups planned. In-person intercept surveys were administered to bridge users via fieldworkers with tablets, gathering data on demographics, transport modes, reasons for use, and its impact on physical activity, wellbeing, and transport. Data were analysed using descriptive statistics. Results: Baseline intercept surveys were conducted with n = 690 respondents (51% male, 77% car owners). When surveyed, 93% of respondents were walking, with 69% reporting their journey was for recreation and 10% for commuting to/from work. Almost two-thirds (64%) stated that the bridge’s opening helped them increase their regular physical activity, for 50% of respondents their wellbeing had improved and for 74% their overall satisfaction with life increased. Respondents reported that if the bridge did not exist, 83% would have used a non-active mode or would not have made the journey. The bridge most frequently provided access to tourist/visitor attractions (67%), retail (36%), greenspace (25%), workplace (20%), and family or friends (20%). The most common factors influencing bridge use was liking the surroundings, getting exercise, improving wellbeing, and feeling safe. Overall sentiment was highly positive, with 78% stating they would ‘very likely’ recommend the route. Conclusion: Initial findings suggest that investments in this type of infrastructure can increase physical activity, encourage active travel, enhance wellbeing, improve access to services, and have positive public reception. The evaluation will triangulate data from mobile phone sensors, resident surveys, counters, observations, and ‘go-along’ interviews to assess the comprehensive and longer-term impact of the bridge as it embeds into the community. Support/Funding Source: Natural Environment Research Council